2013
DOI: 10.1371/journal.pone.0074730
|View full text |Cite
|
Sign up to set email alerts
|

The Endogenous Th17 Response in NO2-Promoted Allergic Airway Disease Is Dispensable for Airway Hyperresponsiveness and Distinct from Th17 Adoptive Transfer

Abstract: Severe, glucocorticoid-resistant asthma comprises 5-7% of patients with asthma. IL-17 is a biomarker of severe asthma, and the adoptive transfer of Th17 cells in mice is sufficient to induce glucocorticoid-resistant allergic airway disease. Nitrogen dioxide (NO2) is an environmental toxin that correlates with asthma severity, exacerbation, and risk of adverse outcomes. Mice that are allergically sensitized to the antigen ovalbumin by exposure to NO2 exhibit a mixed Th2/Th17 adaptive immune response and eosinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 94 publications
1
17
0
Order By: Relevance
“…These additional cell types are potential targets for glucocorticoid regulation. The reduced number of IL-17A-expressing cells in certain patients and reduced IL-17A levels in several animal models (35, 36) by glucocorticoids could also be due to glucocorticoid inhibition of trafficking and recruitment of inflammatory cells (37, 38). In contrast to suppression of the recruitment of most leukocytes, a recent report suggests that glucocorticoids actually promote Th17 attraction and retention via upregulation of the airway epithelial production of CCL20 (23), the ligand for CCR6 on Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…These additional cell types are potential targets for glucocorticoid regulation. The reduced number of IL-17A-expressing cells in certain patients and reduced IL-17A levels in several animal models (35, 36) by glucocorticoids could also be due to glucocorticoid inhibition of trafficking and recruitment of inflammatory cells (37, 38). In contrast to suppression of the recruitment of most leukocytes, a recent report suggests that glucocorticoids actually promote Th17 attraction and retention via upregulation of the airway epithelial production of CCL20 (23), the ligand for CCR6 on Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which this effect takes place appears to differ from allergic asthma in that the typical endogenous response of T-helper (Th)2/Th17 is not required. 32 As NO 2 is likely acting as an oxidant, there may be several mechanisms that could contribute.…”
Section: Traffic Relatedmentioning
confidence: 99%
“…Previous studies demonstrated that exposure to 15 ppm NO 2 increased the expression of allergically inflamed mice (Martin et al, 2013). Similarly, excessive mucus production by hyperplastic goblet cells was reported in patients with acute and chronic asthma (Ordonez et al, 2001).…”
Section: Discussionmentioning
confidence: 87%